Maximal Lactate Steady State may mask an underlying physiological turmoil and lead to inappropriate conclusion - Norris, S. R.; Henderson, J.; Hawley, J. A.; Smith, D. J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The notion of sustainable performance or work intensities and in particular the routes of processes that may gradually erode or interfere with the continuation of such relative power outputs is of interest to sport scientists and sport practitioners. Maximal lactate steady state (MLSS) has evolved into a relatively common operational concept centred upon the highest work intensity that can be maintained without a continual rise in blood lactate accumulation (Beneke, 1995). However, theoretically this is a troublesome notion since it assumes that every subsequent minute of MLSS exercise exists under exactly the same set of conditions as the previous minute that may not be reflected by simple lactate evaluation. Therefore, the purpose of this investigation was to examine work intensities around MLSS using a comprehensive range of variables. Methods Twelve trained male cyclists undertook 4 constant load cycle ergometry tests on 4 separate occasions. The four constant loads were set according to previously determined individualised `lactate minimum power` outputs (LMP, watts) as a quasi-MLSS indicator, such that subjects had to attempt to complete 45 minutes at their LMP-15W, LMP, LMP+15W, and LMP+30W levels. Parameters measured at regular intervals throughout each cycle test included gas exchange variables (i.e., VE, FeO2, FeCO2, VO2, RER), an array of blood markers (i.e., lactate, pH, HCO3, BEecf, PO2, PCO2, SaO2%) and HR. ANOVA with repeated measures was used to examine the parameters over the time course of each test with p=0.05 for all analysis. Results The twelve subjects completed the full 45 minutes for both LMP-15W and LMP, whereas 8 completed the LMP+15W task and only 2 managed the LMP+30W ride. The results in general showed a great level of subject variation at all intensity levels although the LMP-15W and LMP group results showed no significant differences after initial onset of exercise for the key variables (Fig 1.). The higher work intensities (LMP+15 and 30W) showed greater levels of disturbance and statistical differences were observed over time for lactate, pH, HCO3, BEecf, PCO2, VE, and FeCO2. Discussion/Conclusion These results indicate great care must be taken when attributing `steady state` designation to particular work intensities solely on the basis of blood lactate measures and that there is great individual physiological variation when dealing with exercise at and around MLSS/LMP levels. Investigation of gas exchange, blood gas and blood buffer variables reveals an aggressive defence of `sustainable` exercise that `sacrifices` buffer status and allied components (e.g., PCO2, HCO3, BEecf) for pH, and PO2. Interestingly, FeCO2 provides a non-invasive measure with which to examine this defence.